An Investigation Into M-Commerce Perceived Value: Assessing The Digital Transformation Of Shopping Among Millennials And Generation Z In The Eastern Cape - Justino, Mateus Vicente (Journal of Ecohumanism, 2025)
The millennials (generation Y) and generation Z are perceived to be the most attractive and significant segments of the global population for online shopping. However, these segments would show much higher variation in their online shopping in South Africa. With the need to increase productive uses, among other things, in e-commerce and e-banking, this study’s purpose was to examine the m-commerce perceived value among the millennials and generation Z in tertiary education in Butterworth, South Africa, and provide recommendation based on their actual technological value perception. The quantitative research approach and the cross-sectional study design was used. Surveymonkey.com was used as the survey tool to collect data. The study employed the cluster sampling technique to approach the participants. Findings show that perceived usefulness continues displaying a prominent position as a driver of the use of recent technologies. Amongst the value perceptions of the m-commerce use by the millennials and generation Z, perceived usefulness was the dominant, followed by ubiquity, monetary value, information value, convenience, and social value. Recommendations made on the basis of the empirical study and suggestions for future research are proposed.